2014
DOI: 10.1097/hjh.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the major gene regulating serum uric acid associates with clinic SBP and the white-coat effect in a family-based study

Abstract: Results in this family-based study are compatible with the hypothesis that uric acid is a causal risk factor for hypertension. Trials testing uric acid-lowering interventions are needed to definitively establish the causal implication of hyperuricemia in human hypertension. [Corrected]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 30 publications
0
23
0
3
Order By: Relevance
“…Meanwhile, Mendelian randomization studies of genes known to influence uric acid levels have shown that while a genetic predisposition toward hyperuricemia is associated with high risk of gout, it is not associated with higher risk of hypertension (42). However, even these findings are inconsistent with some gene studies showing an association (43,44) and others showing no association (4547). …”
Section: Discussionmentioning
confidence: 66%
“…Meanwhile, Mendelian randomization studies of genes known to influence uric acid levels have shown that while a genetic predisposition toward hyperuricemia is associated with high risk of gout, it is not associated with higher risk of hypertension (42). However, even these findings are inconsistent with some gene studies showing an association (43,44) and others showing no association (4547). …”
Section: Discussionmentioning
confidence: 66%
“…These findings are in contrast to a study by Kleber et al [14] wherein a genetic risk score for high uric acid including eight gene variants was related with cardiovascular death. Moreover, in a study by Mallamaci et al [15], a different SNP in the SLC2A9 gene was associated with higher serum uric acid and higher SBP. This was in agreement with a careful analysis of an Amish cohort that revealed an association between a variant of the SLC2A9 gene and hypertension [16].…”
Section: Genetic and Environmental Factors Associated With Serum Uricmentioning
confidence: 96%
“…16 In addition, a recent article by Mallamaci et al 17 showed that rs7345555 variant in SLC2A9 gene is associated with systolic blood pressure in 449 cardiovascular complication-free individuals. In another Mendelian Randomization study, Palmer et al 18 studied the association of a variant in SLC2A9 gene with systolic and diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%